Perbandingan Efektivitas Regulasi Perlindungan Konsumen Antara Indonesia Dan Jepang - Mulyana, Haidee (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2026)
This research aims to analyze the comparative effectiveness of consumer protection regulations between Indonesia and Japan in response to rapid technological developments and online transactions. The method used is normative legal research with a statutory and comparative approach using secondary data. The results show that Indonesia has an advantage in the aspect of legal substance because it has a single general consumer protection law formulated based on comprehensive academic papers. Conversely, Japan implements a fragmented regulatory system without a single general umbrella law but excels in legal enforcement structures and legal culture through periodic public awareness surveys conducted by the government. The factors most influencing legal effectiveness in both countries include legal substance, enforcement structures, public legal culture, and external factors such as technological advancement. In conclusion, Indonesia is more effective in norm formulation, while Japan excels in addressing social realities and institutional strengthening.